A fragment of a tenth-century English sacramentary. (26th April 2019) - Hartzell, K. D.
Abstract: An abiding concern for scholars of the presence of music in Anglo-Saxon England is whether parochial witnesses can reflect a more comprehensive reality. This article discusses a hitherto undiscovered source of information pertinent to this topic. Its conclusions are not as precise as one would want, due to the source's fragmentary nature, but they help us address music in a wider world nevertheless.